The Effect of Special Exercises Using Rubber Ropes on The Development of Some Physical Abilities and Achievement in F56 Female Discuses Thrower Class - wadah, ahmed; Shaghati , Ahlam (Journal of Physical Education, 2022)
The research aimed at deigning special exercises using rubber ropes for developing some physical abilities and achievement in (F56) female discus throwers as well as identifying the effect of these exercises in the development of some physical abilities and achievement in (F56) female discus throwers. The researchers used one group the experimental method on wheelchair discus throwers class F56 for eight weeks with three training sessions per week using high intensity circuit training. The data was collected and treated using proper statistical operations to conclude that the designed exercises developed some physical abilities and achievement in (F56) female discus throwers. In addition to that, high intensity circuit trainings is suitable for female discus throwers class F56 because it develops physical and motor abilities as well as their performance.